Cell-based screening test for idiopathic scoliosis using cellular dielectric spectroscopy - Akoume, Marie-Yvonne; Azeddine, Bouziane; Turgeon, Isabelle; Franco, Anita; Labelle, Hubert; Poitras, Benoît; Rivard, Charles-Hilaire; Grimard, Guy; Ouellet, Jean; Parent, Stefan; Moreau, Alain (Spine (Philadelphia, Pa. 1976), 2010)
A cell-based assay was developed to identify asymptomatic children at risk of developing idiopathic scoliosis (IS) and to stratify IS patients at an earlier stage in order to better predict their clinical outcome. Clinical validation of this assay was performed by testing IS patients at different stages, healthy control subjects, and asymptomatic offspring, born from at least one scoliotic parent, who are considered at risk of developing this disorder. Our goal was to develop and validate a clinical test for IS using cellular dielectric spectroscopy (CDS) and peripheral blood mononuclear cells (PBMCs). We have previously demonstrated the occurrence of a melatonin signaling dysfunction in osteoblasts obtained from severely affected IS patients using a cAMP assay. This led us to stratify IS patients into 3 functional subgroups. A group of 44 patients with IS was compared with 42 healthy control subjects and 31 asymptomatic at-risk children. PBMCs were obtained after centrifugation on a Ficoll-gradient. Melatonin signal transduction was measured by CDS in the presence of varying concentrations of melatonin or iodomelatonin. Osteoblasts from distinct functional subgroups were retested using CDS, allowing their classification into the same functional subgroups with both ligands as initially demonstrated using a cAMP assay. Clinical data obtained with CDS and PBMCs showed 100% specificity and 100% sensitivity because melatonin signaling impairment was observed only in IS patients and not in healthy controls. Assessment of the risk of developing a scoliosis in asymptomatic children was determined by CDS in 33% of asymptomatic children at risk, which was confirmed clinically within 24 months. This cell-based assay can serve as a presymptomatic screening test to identify asymptomatic children at risk of developing IS and may be used to improve stratification of patients, which in turn allow clinicians to predict their clinical outcome. Moreover, this functional blood test is advantageous because it can be performed without prior knowledge of specifically mutated genes causing IS.